The purification and immunological isolation of ATP citrate lyase from rat liver : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University, New Zealand - Walker, Brett Keith (Massey University, 1986)
ATP CITRATE LYASE (E.C 4.1.3.8) has been purified from rat hepatocyte cytoplasm by a combination of existing published procedures. The final purification method produced homogeneous ATPCL with specific activity of 10-16 units/mg. Antibodies were raised in rabbits against purified ATPCL eluted from reactive Blue Sepharose CL-68 or DEAE anion exchange column. The purified antibodies were tested for their specificity for ATPCL. This was accomplished by Ouchterlony double diffusion analysis and also by disruption of antibody-antigen complexes and visualizing the gene rated protein bands on detergent gels. The equivalence point of the purified antibody was determined by immunotitration with both purified enzyme and crude extract. The equivalence point was later confirmed by immunotitration of radiolabelled proteins. Antibodies were then used to immunochemically isolate and quantitate the amount of (35-S) methionine or (14-C) radiolabelled ATPCL in the cytosolic fraction of rat liver. Pulse labelling of rat liver proteins in vivo and then precipitation of radiolabelled proteins demonstrated that the purified antibodies precipitated proteins other than just the ATPCL subunit. The amount of ATPCL present in the cytosolic fraction could be calculated after immu noprecipitation and excision of radiolabelled ATPCL subunition SOS-PAGE. The proportion of ATPCL protein to the total TCA precipitable protein could then be calculated since the immunoprecipitation was carried out under conditions of antibody excess. Radiolabelled ATPCL was then immunoprecipitated from the cytosolic fractions of rats that had been subjected to different nutritional regimes. The results of this set of experiments showed that induction of ATPCL activity resulted from an increase in immunologically reactive protein. Increasing amounts of radiolabelled immunoreactive ATPCL protein could be precipitated by antibodies as the enzyme was induced. Induction of ATPCL activity resulted from increased rate of synthesis or decreased rate of degradation of immunoreactive protein and not from the activation of pre-existing enzyme protein.
Keywords: Adenosine triphosphatase; Purification; Lyases